王里剧作与演出研究 = A study of Wang Li ‘s plays and performances - 谢秀彬 Seah, Siew Ping (2010)
王里是活跃于六七十年代的新加坡剧作家。 在他的剧作中，有不少与国家政策呼应的题材。相较于该时代的剧本，王里书写的题材是较少见的。 尤其在六七十年代，左派思想 仍算是新加坡的主流思潮，王里的剧本和演出在当时便有了一种相当特殊的社会位置。本论文将通过整理出王里的生平与剧作演出来探讨他的剧作在该时代的意义及其演出的特点，同时沿着这个时代脉络分析王里的剧本， 理解他的剧本如何与该时代的政治和社会环境呼应。Wang Li was a local playwright active in the theatre scene during the sixties and seventies. Many of his plays corresponded to the country’s policy then. As compared to the themes of play in that era, the topics in Wang’s writing were relatively rare, especially in times when the leftist was prominent. The plays and the performance hence had a unique position in the society. Through understanding the life and work of this playwright, this thesis aims to explore the significance of his works, at the same time, tries to understand how his play correspond to the society and political environment then.